Ensaios sobre desemprego, capital humano e progresso tecnológico - Pereira, Daisy Caroline Nascimento (2022)
The thesis is composed of three essays on the determination of longterm unemployment from a postKeynesian perspective, in which the role of education and technological progress are emphasized. The first essay presents a postKeynesian macroeconomic model that verifies conditions for the existence of unemployment in the short and long term. It is an extension of the Stockhammer (2004) model that does not consider the effects of technological progress on unemployment. The relationships between the model variables are estimated through a Vector Autoregressive Model (VAR). Technological progress is included and endogenously determined from the variation in the employment rate. In the long run, it appears that the effects of technological progress on unemployment will depend on whether the economy has a wageled or profitled growth regime. Next, the second essay presents a Kaleckian model of economic growth and employment in the long term, in which the expenditure on education made by workers is relevant to the economic dynamics through the perspective of aggregate demand. The level of employment, the overall growth rate of labor productivity and expenditure on education are endogenously determined, the latter being based on the share of wages in national income. The medium and longterm equilibrium values are path dependent. Furthermore, higher spending on education reduces the share of profits in national income, but increases the rate of profit of capitalists. Finally, the third essay empirically tests the shortand longterm effects of human capital and technological progress on the employment rate in the period 19602019 for two groups of countries, developed and developing. Therefore, we seek to test the hypothesis that technological progress destroys jobs at a faster rate than education creates from the formation of human capital. The results validate the hypothesis only in the short term, in which technological progress destroys employment and education and human capital do not present statistically significant effects. In the long run, education and human capital stimulate employment and the effect of technological progress is positive for developed countries and negative for developing countries.